Nitrogen-functionalized carbon-supported Pt catalysts implemented in high-temperature polymer electrolyte membrane fuel cell - Pimperl, Nicole; Bevilacqua, Nico; Schmid, Michael A.; Loichet Torres, Paulette A.; El-Sayed, Hany A.; Zeis, Roswitha; Zeyer, Klaus Peter (Journal of Power Sources, 2021)
Nitrogen-modified carbon supports were investigated in the catalyst layer of a high-temperature polymer electrolyte membrane fuel cell (HT-PEMFC) with respect to fuel cell performance, kinetic, and transport-related voltage losses. Catalysts with different amounts of nitrogen functional groups (NHx) were synthesized and characterized by elemental analysis, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). The interaction between the nitrogen-containing functional groups and the phosphate ions was investigated in RDE experiments. The experiments showed that in the case of the nitrogen-functionalized catalysts, the activity is reduced by a factor of up to 2 compared with a commercial Pt/C catalyst in 0.1 M HClO4 + 0.05 M H3PO4. The interaction was further confirmed by membrane electrode assembly (MEA) testing. Impedance spectra and distribution of relaxation times (DRT) analysis were used to pinpoint the voltage losses of the fuel cell. We show that a low amount of nitrogen-containing functional groups improves performance; this can be attributed to the improved phosphoric acid distribution in the catalyst layer. This method can successfully control the acid distribution but must be fine-tuned for extended cell operation.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Distribution of relaxation times (DRT) analysis; High-temperature polymer electrolyte membrane fuel cell (HT-PEMFC); Nitrogen-modified carbon supports